Sleep, Positive Affect, and Circulating Interleukin-6 in Women With Temporomandibular Joint Disorder. Issue 3 (24th April 2022) - Hunt, Carly A.; Mun, Chung Jung; Owens, Michael A.; Lerman, Sheera F.; Kunatharaju, Shriya; Tennen, Howard A.; Buenaver, Luis F.; Campbell, Claudia M.; Haythornthwaite, Jennifer A.; Smith, Michael T.; Finan, Patrick H.
ABSTRACT: Objective: Systemic inflammation is commonly observed in idiopathic chronic pain conditions, including temporomandibular joint disorder (TMD). Trait positive affect (PA) is associated with lower inflammation in healthy controls, but those effects may be threatened by poor sleep. The associations between PA with proinflammatory cytokine activity and potential moderation by sleep in chronic pain are not known. We thus investigated the association between PA and circulating interleukin-6 (IL-6) and moderation of that association by sleep in a sample of women with TMD and sleep difficulties. Methods: Participants ( n = 110) completed the insomnia severity index and provided blood samples at five intervals throughout an evoked pain testing session. They then completed a 14-day diary assessing sleep and affect, along with wrist actigraphy. Results: There was not a significant main effect of PA on resting or pain-evoked IL-6 ( b = 0.04, p = .33). Diary total sleep time ( b = −0.002, p = .008), sleep efficiency ( b = −0.01, p = .005), sleep onset latency ( b = 0.006, p = .010), and wake after sleep onset ( b = 0.003, p = .033) interacted with PA to predict IL-6, such that PA inversely predicted IL-6 at higher levels of total sleep time and sleep efficiency and at lower levels of sleep onset latency and wake after sleep onset. Surprisingly, when sleep was poor, PA predicted greater IL-6. Conclusions: The potential salutary effects of PA on resting IL-6 erode when sleep is poor, underscoring the importance of considering sleep in conceptual and intervention models of TMD.